Improvement on Alcohol Breath-Analyzer Ethanol Biosensor based on Roselle-Chitosan Blend - Ahmed M. S. Eljali; Irwana Nainggolan; Shahrir Hashim; Tulus Ikhsan Nasution (Institute of Advanced Engineering and Science, 2017)
This paper presents a study on designing of a breath-analyzer ethanol biosensor through vaporization technology. A roselle extract and chitosan smart gel were used to fabricate the bio-sensing material. Sol-gel electrochemical deposition method was used to coat a thin film of the sensing material blend on patterned golden surface printed circuit board. Differentiation, response time and repeatability properties were studied by exposing 100ppm, 50ppm and 25ppm of ethanol vapor to the breath-analyzer. The accuracy of the breath-analyzer was tested by using I-V electrical testing. The analyzed data demonstrated that the breath-analyzer ethanol biosensor is capable of identifying the concentration of ethanol vapor at room temperature successfully, which can be used as analyzer of alcohol concentration when the sensor exposed to the exhale breath. The roselle-chitosan film sensors have shown the characteristic of a reliable sensor i.e. good sensitivity, selective, repeatable, able to recover and stable.